THE RELATIONS BETWEEN BODY COMPOSITION AND MOTORICAL SKILLS BY THE CHILDREN OF AGE 7 - Sabolč Halaši; Josip Lepeš (Sport Mont, 2012)
On the example of 125 respondents, 65 boys and 63 girls at 7.39 decimal years, who attended first grade at Primary Schools „Majšanski Put“ and „Jovan Jovanovic Zmaj“ from Subotica, basical antropometrical characteristics are measured, general motorical skills are proved on the basis of 7 motorical tests, body composition is showed by In Body 230 machine. With regressive analysis it is proved that the predictorical system of variables for the percentage of body composition (the whole quantity of body fat, water and muscles) is statistically significantly connected with the criteria defined as general motorical factor and with that it is described that 39 % of boys and 34 % of girls have the same variables. Standardized regressional coefficient showed that by boys and girls at 7.39 decimal years the whole quantity of body fat and body weight have a statistically negative influence on general motorics, and by girls body height has a statistically positive influence on it.